Trinidad, Traveller's Palm - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
This postcard shows the Traveller's Palm which has a distinctive fan shape and was given its name because the sheaths of the stem hold drinking water which can be used as an emergency drinking supply.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Traveller's Palm; Ravenala madagascariensis